Densification of Mn-doped tin oxide films by conventional heating and microwave heating treatment - Rizzato, A. P. [UNESP]; Santilli, Celso Valentim [UNESP]; Pulcinelli, Sandra Helena [UNESP]; Stuerga, D.; Chaumont, D.; Briois, V. (IOP Publishing, 2005)
Mn(II) doped SnO2 thin films used for shielding fluoride glasses against corrosion were investigated by x-ray absorption spectroscopy (EXAFS and XANE)S at the Sn and Mn K-edges. The effect of firing treatment on the densification of the films was studied. It has been evidenced a partial change of Mn valence from 2.3 to 2.6 upon heating which is attributed to a change of ratios of two Mn sites: grafted divalent Mn ions at the surface of SnO 2 nanocrystallites and trivalent Mn ions embedded into a substitutional solid solution with Sn. © Physica Scripta 2005.
Keywords: Densification; Extended X ray absorption fine structure spectroscopy; Manganese; Microwave heating; Tin dioxide; Fluoride glasses; Tin oxide films; Oxide films